Menanamkan Nilai-Nilai Islami Pada Anak Usia Dini 3-6 Tahun Melalui Metode Bermain Peran - Lailatul Huda; Rina Syafrida; Ine Nirmala (PIAUD Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah, 2020)
ABSTRACT This study aims to make it easier for teachers to provide guidance and learning about Islamic values ​​to children so that they can more clearly know each child's characteristics when learning is carried out using the role-playing method in the classroom and make it easier for children to understand someone's good and bad qualities and learn to apply values. Islamic for children as early as possible by way of role playing. Data obtained from the Purwakarta Department of Education. This research uses a qualitative descriptive case study. The subjects of this study were children 3-6 years of age. The results showed the application of role playing can be used as a tool for development in instilling Islamic values, this can be seen in previous research. Keywords: Embedding Islamic Values, Early Childhood, Role Playing